2005
DOI: 10.4049/jimmunol.174.1.517
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages Expressing Triggering Receptor Expressed on Myeloid Cells-1 Are Underrepresented in the Human Intestine

Abstract: Triggering receptor expressed on myeloid cells (TREM)-1 is a cell surface molecule on neutrophils and monocytes/macrophages implicated in the amplification of inflammatory responses by enhancing degranulation and secretion of proinflammatory mediators. Macrophages play an important role in the intestinal mucosal immune system, because they are preferentially localized in the subepithelial region. Despite the presence of enormous numbers of bacteria in the colonic mucosa and the close proximity between mucosal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
91
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(97 citation statements)
references
References 32 publications
4
91
2
Order By: Relevance
“…Whereas similar inhibitory effects of TNFα on TREM-2 have been described in monocyte-derived dendritic cells (Bouchon et al, 2001a), published reports on the effects of TNFα on TREM-1 expression are conflicting. Thus, while some studies have shown that TNFα upregulates TREM-1 expression in mononuclear phagocytes, others report no effect (Bleharski et al, 2003;Knapp et al, 2004;Murakami et al, 2006;Schenk et al, 2005). Differences in these results and our studies may be due to distinct origin of the macrophages examined and/or the culture conditions.…”
Section: Discussioncontrasting
confidence: 54%
“…Whereas similar inhibitory effects of TNFα on TREM-2 have been described in monocyte-derived dendritic cells (Bouchon et al, 2001a), published reports on the effects of TNFα on TREM-1 expression are conflicting. Thus, while some studies have shown that TNFα upregulates TREM-1 expression in mononuclear phagocytes, others report no effect (Bleharski et al, 2003;Knapp et al, 2004;Murakami et al, 2006;Schenk et al, 2005). Differences in these results and our studies may be due to distinct origin of the macrophages examined and/or the culture conditions.…”
Section: Discussioncontrasting
confidence: 54%
“…This is also well in line with the notion that the TREM-1 / DAP12 pathway does not itself stimulate the production of pro-inflammatory mediators but it rather lowers the threshold of the inflammatory response to bacterial infection (Klesney-Tait et al, 2006). Engagement of TREM-1 in combination with microbial ligands that activate TLRs can synergistically increase the production of pro-inflammatory cytokines, including IL-1 β, IL-6, IL-8, monocyte chemotactic protein-1 and tumor necrosis factor-α in monocytes and macrophages (Bleharski et al, 2003;Bouchon et al, 2000;Schenk et al, 2005;Schenk et al, 2007), hence amplifying the inflammatory response to bacterial challenge (Netea et al, 2006). P. gingivalis has a known capacity to induce pro-inflammatory cytokine production by monocytes (Bostanci et al, 2007a;Bostanci et al, 2007b;Hamedi et al, 2009), but the potential synergism of TREM-1 has never been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…IL-10, another relevant immunomodulatory cytokine produced under physiological conditions in the intestinal lamina propria, might also influence the functional properties of intestinal macrophages either by directly dampening monocyte/macrophage functions or indirectly by upregulating TGFβ production in distinct cell types, including immature DCs and macrophages [61][62][63]. Intriguingly, monocytes cultured in the presence of recombinant TGFβ alone or together with IL-10 did not gain an intestinal macrophages-like phenotype such as absence of CD14, whereas IL-10 and TGFβ synergistically downregulate CD89 and TREM-1 surface expression on blood monocytes and prevented the upregulation of these markers by proinflammatory stimuli such as LPS or TNF [54]. This indicates that, in addition to IL-10 and TGFβ, other intestinal mucosa-derived factors and cognate cell-cell interactions may be required for the full differentiation of recruited monocytes into resident intestinal macrophages.…”
Section: Regulation Of Phenotype and Functions Of Intestinal Macrophagesmentioning
confidence: 99%
“…This is in sharp contrast to most other tissue macrophages and blood monocytes. Intestinal macrophages also mostly lack the triggering receptor expressed on myeloid cells-1 (TREM-1), an efficient amplifier of acute and chronic inflammatory reactions that is generally expressed on peripheral blood neutrophils and most monocytes and macrophages of secondary lymphoid organs [54]. Engagement of TREM-1 on TREM-1-positive myeloid cells leads to enhanced secretion of proinflammatory mediators (e.g., TNF, IL-1β, MCP-1, IL-6, and IL-8) by monocytes, upregulates several cell surface molecules (e.g., CD40, CD86, and CD32) on monocytes, and prolongs the survival of TREM-1-positive inflammatory cells [54,55].…”
Section: Distinct Properties Of Intestinal Lamina Propria Macrophagesmentioning
confidence: 99%